ACCOUNTABILITY IN THE MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS FOR IMPROVING EDUCATIONAL QUALITY AT SMK MA'ARIF NU 2 KARANGLEWAS - Astuti, Astuti; Hanif, Muh. (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to conduct an in-depth analysis of the accountability-based management of School Operational Assistance (BOS) funds to improve the quality of education at SMK Ma'arif NU 2 Karanglewas, Banyumas Regency. Although various previous studies have highlighted the importance of transparency and accountability in the management of BOS funds, research that specifically focuses on vocational school contexts remains limited. In fact, vocational education has its own complexities, particularly concerning the need for practical facilities, the strengthening of productive teachers' competencies, and the governance of expertise programs. This research gap indicates the necessity of providing a more detailed analysis of how accountability practices can directly contribute to improving the quality of educational services in vocational institutions. This study employs a qualitative approach using a case study method, enabling the researcher to obtain a comprehensive understanding of the dynamics of BOS fund management within the educational unit. Data were collected through in-depth interviews with the principal, BOS treasurer, teachers, and the school committee. Field observations and document analysis-including financial reports and records of budget realization-were used to enhance the validity of the findings. The results show that SMK Ma'arif NU 2 Karanglewas has implemented accountability principles through systematic and transparent financial reporting, the active involvement of the school committee in planning and monitoring processes, and the provision of publicly accessible information. These accountability practices have made a tangible contribution to improving learning facilities and infrastructure, strengthening the quality of teaching and learning processes, and enhancing teacher professionalism. Thus, the accountability of BOS fund management functions not only as an administrative obligation but also as a strategic foundation for building public trust and strengthening community participation in the continuous improvement of educational quality.